Comparative Financial Performance Of Sharia Business Units Of Regional Development Banks In Java Island Based On The Islamicity Performance Index - Rohman, Muhammad Aris Taufiqur Rohman; Lu'lu'il Maknuun, Lu'lu'il Maknuun (Masoem University, 2026)
While Islamic Regional Development Banks (RDBs) in Indonesia showed significant asset growth reaching IDR 73.5 trillion in 2022, performance across individual units remains uneven, necessitating a deeper evaluation beyond conventional metrics. This study aims to evaluate and compare the financial performance of Sharia Business Units (SBUs) of RDBs across Java Island during the 2019–2023 period using the Islamicity Performance Index (IPI). A quantitative comparative method was employed, focusing on four purposive samples: SBU RDB JATIM, JATENG, DIY, and DKI, using secondary data from annual financial statements. The performance was measured through four key IPI indicators: Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), and Islamic Income vs. Non-Islamic Income (IInc vs. NIInc). The results reveal that while all SBUs achieved a perfect score of 100% in the IInc vs. NIInc indicator, significant challenges persist in other areas, as PSR, ZPR, and EDR scores mostly fell below the